Soil as a Source of Fungi Pathogenic for Public Health - Isabella Grishkan (Encyclopedia, 2024)
Soil is an environment for huge diversity of fungi, which fulfill various tasks and support the maintaining of soil health. At the same time, varieties of soil fungal species, which produce numerous airborne spores and a range of mycotoxins, are known to be pathogenic for human health. The present review aims to summarize the current knowledge on soil fungi causing public health problems, including dermatoses, allergies, pulmonary diseases, wound infections, infections of the central nervous system, etc.